Oncolytic virotherapy: potentially a game-changing tumor treatment - Keßler, Tobias; Wick, Wolfgang (Cancer cell, 2021)
A two-center phase I trial published in the New England Journal of Medicine shows safety and feasibility of locally administered oncolytic herpes simplex virus-1 virus plus 5 Gy radiation for progressive pediatric high-grade gliomas. Patients seemed to have an unusually good clinical course and showed immune activation in post-treatment tissues.